Manajemen Perencanaan Sarana Dan Prasarana di SMAN 1 Serbajadi Kabupaten Serdang Bedagai - Amiruddin Siahaan; Suwandi Suwandi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2021)
The purpose of this study was: to determine the natural setting of the founding of SMAN 1 Serbajadi School. To find out the process of planning facilities and infrastructure at SMAN 1 Serbajadi School. To find out the procurement of facilities and infrastructure at SMAN 1 Serbajadi School. To find out the use of facilities and infrastructure at SMAN 1 Serbajadi school. To know the maintenance of infrastructure at SMAN 1 Serbajadi School. Management of educational facilities and infrastructure according to Rohiat is an activity that regulates to prepare all equipment/materials for the implementation of the educational process in schools. Management of facilities and infrastructure is needed to help the teaching and learning process run smoothly.Â This study uses a qualitative method. Researchers describe the findings of the phenomena that occur in the field. The main data source is the principal as a key informant, followed by a snowball process. Data collection was carried out using observation techniques, interviews, and documentation studies regarding the management of facilities and infrastructure at SMAN 1 Serbajadi School.Â The results of this study, the authors can conclude that the management of educational facilities and infrastructure at the Darunsat Witya School, includes: planning, procurement, use and maintenance. As a supporter of success are educational facilities and infrastructure. So it is hoped that the teaching and learning process can be even better.